RELATED PARTY CONCEPT, TRANSFER PRICING CORRECTION DISPUTES, MUTUAL AGREEMENT PROCEDURE (MAP) SUBMISSION: INDONESIA CASE - Ilham, Muhammad; Widiastuti, Budiasih; Firmansyah, Amrie (Kesatuan Press, 2022)
This research aimed to determine the concept of related parties between countries as the entry point for resolving the dispute over Transfer Pricing (TP) through Mutual Agreement Procedure (MAP). This research was conducted with qualitative methods to observe the phenomena in the practices of related parties and their relation to the submission of MAP. The data employed are primary in structured interviews and content analysis sourced from research results and regulations issued by the government. The results of this study indicate that to be resolved through MAP, a Transfer Pricing correction dispute must occur between two countries that have the same interpretation of the determination of the related parties. So, not all TP correction disputes across countries can be resolved through MAP because each country has autonomous rights to define related parties differently.